ISLAMIC EDUCATION PARADIGM BASED ON COMMUNITY DEVELOPMENT STRATEGY OF CURRICULUM DEVELOPMENT AND EXTRACURRICULAR ACTIVITIES BASED ON CBE AT DAARUSH SHOLAH ISLAMIC BOARDING SCHOOL, EAST KUTAI - Muafin, Siti Akhlis; Zamroni, Zamroni; Al Anshori, Habib Anwar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This community-based Islamic education is an approach that combines Islamic values with efforts to improve community empowerment through education. In the context of the Daarush Sholah Islamic Boarding School in East Kutai, the application of this paradigm focuses on curriculum development and extracurricular activities based on competency-based evaluation (CBE). CBE provides opportunities for students to develop according to their abilities and needs, while strengthening the relationship between education and community empowerment. This study aims to explore the strategy of curriculum development and implementation of CBE-based extracurricular activities at the Daarush Sholah Islamic Boarding School in East Kutai.